Education as Welcoming: A Proposal based on Levinas’ Ethics - Ortega Ruiz, Pedro (2024)
Emmanuel Levinas, one of the most profoundly original western philosophers of the 20th Century, has attracted considerable attention in recent years amongst educators and philosophers of education. His thought has several ethical implications for education in areas related with moral education, diversity issues, multiculturalism, or recognition policies. This paper is based on Levinas’ claim that the concept of responsibility builds the cornerstone of his philosophical work, and that responsibility is most clearly manifested in the welcoming of the other. To educate is to welcome, to accompany and to help the pupil in its life plan. According to Levinas’ ethics, welcoming is not understood as a mere object of instruction or teaching: “learning” takes place through contagion, through mimesis. Therefore, the paper criticizes an approach that stresses previously programmed concrete teaching activities, and defends the need to create a teaching environment in the classroom that encourages openness to the other, especially to those who are culturally different. It concludes showing the importance of a welcoming teaching that explores the feeling of responsibility and takes the experience of the pupil as the starting point of teaching action.